DESIGN OF THE LOW-LEVEL CONTROL SYSTEM IN LONGITUDINAL CHANNEL OF AN UNMANNED HELICOPTER - A. M. Bronnikov; E. O. Karavashkina; V. S. Kulabukhov; A. Yu. Chekin (Научный вестник МГТУ ГА)
This paper describes the design of the collective pitch control law of an unmanned helicopter in low-level altitude mode. The novelty is using an adaptive inner-loop control with an identifier and a reference model, which automatically provides disturbance compensation in the altitude channel during roll and yaw arbitrary maneuvering. The outer-loop control provides radio altitude hold with desired gain-frequency characteristic of stabilization error.